2012
DOI: 10.1021/ja308167f
|View full text |Cite
|
Sign up to set email alerts
|

Nanofluidic Ion Transport through Reconstructed Layered Materials

Abstract: Electrolytes confined in nanochannels with characteristic dimensions comparable to the Debye length show transport behaviors deviating from their bulk counterparts. Fabrication of nanofluidic devices typically relies on expensive lithography techniques or the use of sacrificial templates with sophisticated growth and processing steps. Here we demonstrate an alternative approach where unprecedentedly massive arrays of nanochannels are readily formed by restacking exfoliated sheets of layered materials, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
431
3
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 450 publications
(451 citation statements)
references
References 36 publications
(59 reference statements)
16
431
3
1
Order By: Relevance
“…After curing, two reservoirs were carved out in the PDMS device to expose the two ends of the membrane to the electrolyte solutions. More details about our device making process can be found in our previous article 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After curing, two reservoirs were carved out in the PDMS device to expose the two ends of the membrane to the electrolyte solutions. More details about our device making process can be found in our previous article 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been challenging to fabricate channels at this dimension, we have found that they can be rapidly generated in bulk scale and over macroscopic areas by restacking 2D sheets. In an earlier work, we discovered that the spaces between stacked graphene oxide sheets can indeed function as cation-selective nanofluidic channels for electrolytes 12 . Higher-than-bulk ionic conductivity, governed by the surface charge of the channel walls, was observed.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The permeance of water vapour under these conditions is B0.1 l m À 2 Á h À 1 Á bar À 1 under a pressure of 23 mbar 19 . In addition, Raidongia and Huang 20 and Sun et al 21 have reported that ions can transport selectively through the fully wetted GO film via diffusion. However, the permeation through these GO membranes remains insufficient to allow them to compete with commercial pressure-driven ultrafiltration membranes because these membranes are limited by their less fluidic channels (the randomly distributed nanoscale wrinkles 20,22 and/or spaces strutted by functional hydroxyl, carboxyl and epoxy groups) 21,23 and the slow diffusion process therein.…”
mentioning
confidence: 99%
“…This fabrication method is simple, timesaving and easy to scale up when compared with the previously reported fabrication techniques for scalable-reduced GO films. 7,13 In this fabrication process, the GO sheets, after derivatization by carboxylic, phenol hydroxyl and epoxide groups, can readily be exfoliated to form a stable colloidal suspension because they are stabilized by their hydrophilicity and electrostatic repulsion, 14,15 which facilitate the homogeneous arrangement of GO platelets during the preparation of GO films. The subsequent photoreduction can provide appropriate reduction of the GO films and induce effective interlinking of the individual graphene sheets.…”
Section: Introductionmentioning
confidence: 99%